2020
DOI: 10.1097/cce.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Intubation and Its Implications on Outcomes in Critically Ill Patients With Coronavirus Disease 2019 Infection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 11 publications
(16 reference statements)
0
43
0
1
Order By: Relevance
“…Figure 1 shows the flow diagram for study selection. A total of 12 studies [13,14,[18][19][20][21][22][23][24][25][26][27] from Africa, Asia, Europe and America, involving 8944 critically ill patients (7639 early, 1305 late) with COVID-19, were incorporated in our meta-analysis. Table 1 and Additional file 1: Supplementary Table 2 summarize the characteristics and risk of bias assessment of the included studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows the flow diagram for study selection. A total of 12 studies [13,14,[18][19][20][21][22][23][24][25][26][27] from Africa, Asia, Europe and America, involving 8944 critically ill patients (7639 early, 1305 late) with COVID-19, were incorporated in our meta-analysis. Table 1 and Additional file 1: Supplementary Table 2 summarize the characteristics and risk of bias assessment of the included studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 studies [13,14,[18][19][20][21][22][23][24][25][26][27] provided data on all-cause mortality. No statistical heterogeneity was detected (I 2 = 0%).…”
Section: All-cause Mortalitymentioning
confidence: 99%
“…The authors concluded that larger cohort studies were needed to detect a difference in mortality between early and late intubation. Other studies have found no advantage for early or late intubation [ 27 , 30 ]. Current mortality data suggest an advantage for patients in whom intubation is completely avoided, but these data may be confounded.…”
Section: Resultsmentioning
confidence: 99%
“…Later studies providing more complete outcome data had mortality rates from 17% to 36% ( 72 , 73 ). A recent retrospective study of 128 patients with COVID-19 did not find a mortality difference between patients who were intubated early or late in their hospital course ( 74 ). With the available respiratory support measures, it is reasonable to try a stepwise approach, monitoring oxygenation, ventilation, and work of breathing, and then intubating as one would in other clinical circumstances ( 70 ).…”
Section: Discussionmentioning
confidence: 99%